(untitled) (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Presence of family during cardiopulmonary resuscitation is debatable. Doctors and nurses locally believe that family should be kept out of resuscitation. This study explores the attitude of doctors and nurses towards presence of family during resuscitation. Methods: This was a cross-sectional descriptive study conducted at Patan Hospital emergency in January 2017. Medical personnel working in emergency were given a set of questionnaires. The result was descriptively analyzed. Results: Sixty-four doctors and nursing staffs participated in the survey. Fifteen (23%) said that they would never allow presence of family during resuscitation, 37 (58%) said sometimes and 13 (20%) said always. Perception of health workers were, 32 (50%) thought it interferes with work; 25 (39%) legal problem; 33 (51%) bad reaction to the team; 35 (54%) psychological trauma to family; 23 (36%) difficult to stop resuscitation; 23 (36%) offence to family; 17 (26%) increase staff stress; 8 (12%) not culturally acceptable and 6 (9%) had no such practice observed. Conclusions: Family presence during resuscitation was not desirable for majority of medical person working at emergency department of Patan Hospital.